2009
DOI: 10.1016/j.rmed.2009.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Chronic airflow obstruction and markers of systemic inflammation: Results from the BOLD study in Iceland

Abstract: In a random population-based sample both CRP and IL-6 were significantly related to lower spirometric values. The association with CRP was stronger in men than in women. This finding underscores the possible importance of systemic inflammation in irreversible airflow limitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
62
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 25 publications
10
62
1
Order By: Relevance
“…6,11,48 This association has been demonstrated in a number of populations, including young, disease-free individuals, the elderly, and populations with and without COPD, but other than in this and our previous report, SCI has not been studied previously. The specific inflammatory biomarkers examined have varied across these studies, but CRP and IL-6 are the most consistently examined.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…6,11,48 This association has been demonstrated in a number of populations, including young, disease-free individuals, the elderly, and populations with and without COPD, but other than in this and our previous report, SCI has not been studied previously. The specific inflammatory biomarkers examined have varied across these studies, but CRP and IL-6 are the most consistently examined.…”
Section: Discussionmentioning
confidence: 46%
“…[1][2][3][4][5][6][7][8][9][10][11] Some, [12][13][14][15] but not all, 16,17 longitudinal studies have observed such associations. Fewer studies have demonstrated cross-sectional associations with biomarkers of oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, cytokine-induced sickness behaviour includes subjective reports of lethargy and tiredness [31], while experimental animal models show behavioural markers of fatigue [32]. While some people with COPD have measurable systemic inflammation out of proportion to the severity of their airflow limitation, there is an overall association between COPD severity and derangement of inflammatory processes [33,34]. There are, of course, other explanations for fatigue in COPD patients, such as the high oxygen cost of breathing, especially in hyperinflated patients, or the limiting effect of hypoxaemia on activities.…”
Section: Discussionmentioning
confidence: 99%
“…Lung function impairment, as assessed by a reduction in the forced expiratory volume measured in the first second of exhalation (FEV1) and forced vital capacity (FVC), contributes significantly to several major health issues, such as all-cause mortality [1,2], chronic lung disease prevalence (chronic obstructive pulmonary disease (COPD) and asthma) [3,4], and death from cardiovascular disease [5]. Preservation of lung health during ageing [6] through identification of modifiable risk factors is a key research priority.…”
Section: Impaired Lung Function Is Associated With Systemic Inflammatmentioning
confidence: 99%
“…Low-grade chronic systemic inflammation, determined by elevation of C-reactive protein (CRP) and interleukin (IL)-6 is a common mechanistic pathway contributing to reduced lung function [4,5,7] and increased cardiovascular events [8,9]. Systemic inflammation is also a feature of chronic respiratory conditions including asthma and COPD [10].…”
Section: Impaired Lung Function Is Associated With Systemic Inflammatmentioning
confidence: 99%